The Influence of Index Fund Ownership on Share Recall Behavior and Proxy Voting Outcomes: A Qualitative Review - Eri Kusnanto; A. Sigit Pramono Hadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This qualitative literature review examines the influence of index fund ownership on share recall behavior and proxy voting outcomes. Index funds, as passive investors with substantial ownership stakes, have significant power in corporate governance, especially through their voting decisions. Although typically less involved in shareholder activism, their voting behavior can shape corporate outcomes, providing stability in governance. However, the review also highlights concerns about the lack of active scrutiny over management decisions, potentially leading to suboptimal outcomes in companies with weak governance structures. The review compares findings from various studies, emphasizing the evolving role of index funds in corporate governance and their impact on shareholder value. It also discusses the limitations of existing literature and calls for future research to explore the behavior of different types of index funds, as well as the potential influence of ESG factors on corporate decision-making.